Pengaruh Umur, Pendidikan, Dan Jenis Pekerjaan Terhadap Pendapatan Dan Pengeluaran Konsumsi Hewan Peliharaan Di Denpasar - Agustini, Ni Komang Putri; Marhaeni, A. A. I. N. (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 12, Desember 2017 (pp. 2352 - 2582), 2017)
The purpose of this study is to explain the effect of age, education and work on household income and expenditure on dogs in North Denpasar District, as well as the role of income in mediating the influence of age, education, occupation and household expenditure on dogs in North Denpasar District. Samples taken as 99 dog careers by Sampling Accidental method through observation, interview and in-depth interview. Analysis technique used path analysis. The results showed age and education have positive and significant impact on income. Respondents work in the formal sector of income and expenditure are higher than the informal sector. Age and education have positive and significant effect on expenditure. Revenue has positive but unsignificant effect on expenditure. Revenue does not mediate the influence of age, education, and type of work on household expenditure of dog owners in North Denpasar District.